2012
DOI: 10.1136/bcr.2012.006164
|View full text |Cite
|
Sign up to set email alerts
|

The use of the ASET in the diagnosis of ventriculoatrial shunt infection

Abstract: BACKGROUNDVentriculoatrial (VA) shunting has been superseded in popularity by the use of the peritoneal route (ventriculoperitoneal (VP)), mainly because of ease of insertion of the latter. However, a substantial number are still used, either as primary insertions or to replace a persistently failing VP shunt. 1 -3 In addition, a large but unknown number of patients with VA shunts remain in the community, usually without neurosurgical follow-up, 4 and may require medical attention at any time.VA shunt infecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…This isolated leukocytosis lacked a "left shift," making the etiology of her leukocytosis on admission most likely from the demargination of white blood cells induced postictally and less likely an acute neutrophilic response to infection [4]. Prior the literature on shunt nephritis has also shown that many patients who were ultimately diagnosed by renal biopsy did not have the expected signs and symptoms of an infection [5,6]. It is important to take a moment and discuss the pathogen involved with shunt nephritis.…”
Section: Discussionmentioning
confidence: 99%
“…This isolated leukocytosis lacked a "left shift," making the etiology of her leukocytosis on admission most likely from the demargination of white blood cells induced postictally and less likely an acute neutrophilic response to infection [4]. Prior the literature on shunt nephritis has also shown that many patients who were ultimately diagnosed by renal biopsy did not have the expected signs and symptoms of an infection [5,6]. It is important to take a moment and discuss the pathogen involved with shunt nephritis.…”
Section: Discussionmentioning
confidence: 99%